If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 6x = 9 Reorder the terms: 6x + y = 9 Solving 6x + y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 6x + y + -1y = 9 + -1y Combine like terms: y + -1y = 0 6x + 0 = 9 + -1y 6x = 9 + -1y Divide each side by '6'. x = 1.5 + -0.1666666667y Simplifying x = 1.5 + -0.1666666667y
| 7/6x=28 | | 16x-(1.86(x^2))=0 | | -8-5x=3 | | 2/3x+4(4x-19)=24 | | 3x-130+4x=73 | | 58z-86=z-(-18) | | 23x-3x= | | 24+3x=3(7-1) | | .67z-.25=.75z+2.25 | | 2+6y=3x+2 | | 3x+2y=200 | | a^2x+(a-6)=(a+6) | | 44=6.28r | | 3x+27=200 | | -6(m-4)=19-7m | | 2w+3=5-4w | | y=1*390+b | | 4-3+2(1-1)= | | 5x+10(-x+28)=2.25 | | (x+2)+2=x+4 | | -15+19r=25 | | -3(8x-6)+4=190 | | 11x-9x+3=2x+5-2 | | -2(n+2)=21+3n | | a+4(-2)=-4 | | 4-4(q+2)=0 | | 0=3t^2-9t+6 | | -6b=12 | | 2-3x=84 | | -3y+8=4y-6 | | 7(5+3x)=35+835+8x | | -3y+3=-4y-6 |